Feasibility of tidal flow power generation in Singapore - Sabiyahtul Fajriyah Bte Rasid (2011)
Alternative energy is important to prevent our planet from being destroyed. Generating electricity using fossil fuels have put our planet in danger as the carbon dioxide concentration in the atmosphere has increased by more than 30% since the 19th century. Carbon dioxide represents the largest component of the greenhouse gases produced by human activities. Methane, ozone, water vapour and carbon dioxide are the major greenhouse gasses. These greenhouse gasses will continue to absorb infrared radiation coming in from the heat of the Sun. Thus, the greenhouse effect is the increase in the global temperature as the heat is trapped in the atmosphere. This has caused severe consequences on the environment.